Vascular smooth muscle ion channels in essential hypertension - Daghbouche-Rubio, Nuria; López-López, José Ramón; Pérez-García, María Teresa; Cidad, Pilar (Frontiers in Physiology, 2022)
Hypertension is a highly prevalent chronic disease and the major risk factor for cardiovascular diseases, the leading cause of death worldwide. Hypertension is characterized by an increased vascular tone determined by the contractile state of vascular smooth muscle cells (VSMCs) that depends on intracellular calcium levels. The interplay of ion channels determine VSMCs membrane potential and thus intracellular calcium that controls the degree of contraction, vascular tone and blood pressure. Changes in ion channels expression and function have been linked to hypertension, but the mechanisms and molecular entities involved are not completely clear. Furthermore, the literature shows discrepancies regarding the contribution of different ion channels to hypertension probably due to differences both in the vascular preparation and in the model of hypertension employed. Animal models are essential to study this multifactorial disease but it is also critical to know their characteristics to interpret properly the results obtained. In this review we summarize previous studies, using the hypertensive mouse (BPH) and its normotensive control (BPN), focused on the identified changes in the expression and function of different families of ion channels. We will focus on L-type voltage-dependent Ca2+ channels (Cav1.2), canonical transient receptor potential channels (TRPC) and four different classes of K+ channels: voltage-activated (Kv), large conductance Ca2+-activated (BK), inward rectifiers (Kir) and ATP-sensitive (KATP) K+ channels. We will describe the role of these channels in hypertension and we will discuss the importance of integrating individual changes in a global context to understand the complex interplay of ion channels in hypertension